Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1136/bmjopen-2016-012216
|View full text |Cite
|
Sign up to set email alerts
|

Potentially avoidable and ambulatory care sensitive hospitalisations among forced migrants: a protocol for a systematic review and meta-analysis

Abstract: IntroductionThere is an increasing number of forced migrants globally, including refugees, asylum seekers, internally displaced persons and undocumented migrants. According to international law, forced migrants should enjoy access to health services free of discrimination equivalent to the host population, but they face barriers to healthcare worldwide. This may lead to a delay in care and result in preventable hospital treatment, referred to as potentially preventable hospitalisation (PPH) or ambulatory care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…In the process of a systematic review on potentially avoidable and ACS hospitalizations among forced migrants [ 35 ], only few empirical studies have been found on ACS conditions and hospitalizations among asylum seekers and the broader population group of forced migrants. Preliminary results indicate that the indicator has not been widely used to display differences and disparities in access to ambulatory care among forced migrants and the domestic population.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of a systematic review on potentially avoidable and ACS hospitalizations among forced migrants [ 35 ], only few empirical studies have been found on ACS conditions and hospitalizations among asylum seekers and the broader population group of forced migrants. Preliminary results indicate that the indicator has not been widely used to display differences and disparities in access to ambulatory care among forced migrants and the domestic population.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a survey among internal medicine specialists in Germany, a considerable proportion reported not being familiar with the HcV regulations and the ASBA [14]. Quantitative studies reported high unmet needs among adult refugees [15], high odds of emergency department use and avoidable hospitalizations among refugee children compared to non-refugees [16,17]. So far, only one study directly compared healthcare use of refugees using different access models by means of a regional survey, showing an underuse of outpatient healthcare among refugees using the HcV model when compared to refugees who were using the eHC model [18].…”
Section: Introductionmentioning
confidence: 98%
“…10 They further note that timely access to outpatient care can hold economic benefits; for example, due to the early detection and treatment of ambulatory care sensitive conditions in the outpatient sector. 11 This is supported by a growing body of research. [11][12][13][14] The main arguments put forward in favour of the HIC, however, are of normative nature, as they relate to governments' legal and moral duty to provide equitable and non-discriminatory access to healthcare.…”
Section: Healthcare Provision For Asylum-seekers In Germanymentioning
confidence: 97%
“…11 This is supported by a growing body of research. [11][12][13][14] The main arguments put forward in favour of the HIC, however, are of normative nature, as they relate to governments' legal and moral duty to provide equitable and non-discriminatory access to healthcare. 5,15,16 Our study uses the recent introduction of the HIC in Berlin as an opportunity to empirically test some of the above described arguments.…”
Section: Healthcare Provision For Asylum-seekers In Germanymentioning
confidence: 97%